KEPUASAN KERJA SEBAGAI MEDIASI HUBUNGAN ANTARA PERSONALITY DAN KINERJA KARYAWAN - Adnan Rajak; Fadli Ali Taslim (Jurnal Manajemen Sinergi, 2020)
Objective: The purpose of this study are: (1) Knowing andanalyzing the influence of personality on employee performance atSMEs in Ternate City; (2) Knowing and analyzing the effect of jobsatisfaction on employee performance at SMEs in Ternate City; (3)Knowing and analyzing the influence of personality on employeejob satisfaction at SMEs in Ternate City; and (4) Knowing andanalyzing job satisfaction is able to mediate the influence ofpersonality on employee performance at SMEs in Ternate City. Inaddition, the results of this study are expected to provide thefollowing benefits: Theoretical Benefits: To support and enrich thedevelopment of human resource management (HRM).Methodology: The test equipment used is Structural EquationModeling (SEM) using Smart PLS as a statistical test tool.Finding: H1 H2, and H3 are accepted at the 5% confidence levelConclusion: The results showed that: (1) Personality had apositive and significant effect on employee job satisfaction atSMEs in Ternate City; (2) Personality (personality) has nosignificant effect on employee performance at SMEs in TernateCity: (3) Job satisfaction has a positive and significant effect onemployee performance at SMEs in Ternate City; and (4) jobsatisfaction is able to fully mediate the influence betweenpersonality and employee performance.